Psychiatric comorbidity in patients with migraine - Ismail, Haamid; Fayaz, Farhana (International Journal of Advances in Medicine, 2022)
Background: Migraine is a highly prevalent and disabling neurological disorder associated with a wide range of psychiatric comorbidities. The aim of the study was to study the psychiatric comorbidities in patients with migraine. Methods: The study population comprised all the out patients who fulfilled the diagnostic criteria of migraine attending a tertiary care psychiatry hospital over a period of 6 months. A total of 90 cases of migraine seen over a period of 6 months were analysed to know the demographic characteristics, clinical pattern and psychiatric comorbidity. Results: Maximum patients were between 21-40 years of age group (41.1%), females (83.3%), married (74.4%) and housewives (52.2%). 64.5% of study population was literate with a formal education above 10th standard. Migraine without aura was commonest sub-type (65.6%). Noise (75.6%) and sunlight (65.6%) was the most common precipitating factors. Anxiety disorders were the most common comorbid psychiatric disorders (40%), followed by major depressive disorder (24.4%). In 24.6% cases, no psychiatric comorbidity was present. Conclusions: Migraine is comorbid with several psychiatric disorders, including anxiety and depressive disorders. When migraine and a comorbid psychiatric disorder are present, it is important to take both disorders into account in formulating a treatment plan.